THE EFFECT OF USING FISHBOWL STRATEGY ON STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT AT THE ELEVENTH GRADE OF SMAN 2 TEMBILAHAN - Alfoni Farhana Zivah; Agus Mustajib; Samsul Amri (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study was to determine the effect of using the Fishbowl Strategy on students' reading comprehension at SMAN 2 Tembilahan as a problem that students face when reading, particularly in reading comprehension. A fishbowl strategy is useful for students’ skill in reading comprehension. The design of this research was experimental. The population of this research was the eleventh grade of SMAN 2 Tembilahan in the 2021–2022 academic year. This study's population included 69 students from four different classes. The samples for this study were divided into two classes, each with 28 students. The sample for this class is XI.MIPA1 as the control group and XI.MIPA2 as the experimental class. To get the data for this research, the researcher used tests as instruments, which included a pre-test and a post-test. There are 20 items per question on the pre-test and post-test in the form of a multiple-choice test. Four meetings were held as part of the learning process. The findings of this research showed that the average score in the pre-test was 28.9, while in the post-test it was 68.88 for the experimental group. The mean score of the post-test was higher than the mean score of the pre-test. The analysis revealed that T-observed was 5% higher than T-table, at 6,397 versus 2,056, an insignificant 5% difference. Based on the result, it was concluded that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, there is a significant effect of using the fishbowl strategy on students’ reading comprehension at SMAN 2 Tembilahan.